Efektifitas Konseling Menyusui Terhadap Pemberian ASI Eksklusif: Literatur Review - Candrawati, Riska Dwi; Amir, Yufitriana; Misrawati, Misrawati (Jurnal Ners, 2026)
The World Health Organization (WHO) recommends exclusive breastfeeding for the first 6 months of life and continued breastfeeding until 2 years of age. Although exclusive breastfeeding provides many benefits, globally, the rate of exclusive breastfeeding is still low. Therefore, appropriate strategies are needed to address these factors, including breastfeeding counseling. This literature review aims to assess the effectiveness of breastfeeding counseling on exclusive breastfeeding. The search was limited to scientific papers published between 2021 and 2025 that focused on breastfeeding counseling related to exclusive breastfeeding. Three databases were searched: Science Direct, PubMed, and Springer Link. Of the 295 studies obtained, 8 studies were included in the review. Data were analyzed using deductive thematic analysis. This review shows that breastfeeding counseling is effective in increasing exclusive breastfeeding rates and can improve mothers' self-efficacy. Counseling can be provided starting from pregnancy, continuing after delivery and immediately after delivery, and can be conducted individually or in groups, face-to-face, online, or hybrid.